Observing the Intellectual Curiosity of English Education Students in the Class - Arny Irhani Asmin (Institut Agama Islam Negeri Palopo, 2020)
Intellectual curiosity also known as epistemic curiosity, it is one of the important abilities that determines student’s creativity and motivation. There are three main components of epistemic responses is observed in this study, they are observations, thinking and consultations. Through classroom observations and interview, the researcher found out that students need to be encouraged and trained continuously to improve their intellectual curiosity in the class. Data showed that almost all students were not focused on paying attention to the teacher explanations, lack of ideas, rarely ask or respond the questions and not actively participating in group or class discussion. Overall, the students were passive in developing creative ideas and showing lack of motivation to learn in class. Thus, teachers are strongly advised to encourage students’ intellectual curiosity in learning process because curiosity allows students to think creatively, critically, and boost their academic performance.